Econometric Analysis of Online Game Transactions on Digital Economy Growth in Indonesia - Ramadani, Febiola Djangkaru; Atmaja, Bagas Arri (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Digital transformation has made the online gaming industry a complex economic ecosystem. This study analyzes the econometric relationship between Transaction Money Turnover (NPT), Internet Access (AI), Internet Speed (KI), and Net Income (PB) with Economic Growth (PE) using the Ordinary Least Squares (OLS) method in the 2015-2024 time series data. The F test (ANOVA) shows that F counts 9.825 with a significance value of less than 0.001, proving that these four variables are simultaneously significant in influencing Economic Growth. The results of the partial t-test revealed that AI (t = 2.180, Sig. = 0.030) and PB (t = 3.704, Sig. less than 0.001) had a significant positive effect, while NPT (t = -3.323, Sig. less than 0.001) and KI (t = -2.733, Sig. = 0.007) showed a significant negative effect on PE. These findings indicate that the increase in transaction value and speed infrastructure has not been optimally utilized for the real economy. Implicitly, increasing digital literacy and incentives are needed to produce infrastructure as academically the empirical gap between nominal transactions and speed becomes the basis for further study of the integration of behavioral and institutional variables.